Electrical characterization of the slow boron oxygen defect component in Czochralski silicon. Issue 12 (28th October 2015) - Niewelt, Tim; Schön, Jonas; Broisch, Juliane; Warta, Wilhelm; Schubert, Martin
Abstract : We investigated the light‐induced degradation of compensated Czochralski grown n‐type silicon and found a fast‐forming and a slow‐forming component similar to p‐type silicon. A study by means of extended lifetime spectroscopy shows that the "slow" defect introduces two recombination‐active energy levels in the silicon band gap. One level resembles the literature data from p‐type silicon of a donor‐like level at E t1 = E CB – (0.41 ± 0.02 eV). The second level is found at E t2 = E VB + (0.26 ± 0.02 eV) and exhibits a strong acceptor‐like capture asymmetry. The two‐level parameterization constitutes a unified model for the description of the injection dependent lifetime on both p‐ and n‐type silicon and is physically more plausible than previous ones featuring multiple independent centers. A comparison to literature data demonstrates the improved description quality achieved with the new parameterization. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The authors investigate the light‐induced degradation of compensated n‐type silicon. Similar to p‐type they find a two‐component degradation and associate it to boron oxygen defects. They show that the "slow" defect introduces two energy levels in the silicon band gap and establish a model for the lifetime limitation due to boron oxygen defects, which is physically more plausible than previous ones.